2021
DOI: 10.3390/pathogens10020198
|View full text |Cite
|
Sign up to set email alerts
|

Toxocara cati and Other Parasitic Enteropathogens: More Commonly Found in Owned Cats with Gastrointestinal Signs Than in Clinically Healthy Ones

Abstract: Intestinal parasites are involved in the health and wellbeing of cats and some of them, due to their zoonotic potential, represent a problem for public health. This study aimed to assess the prevalence of parasitic infections in cats with gastrointestinal signs. Fecal samples collected from 137 cats were analyzed by the flotation method using a sodium chloride saturated solution. The overall prevalence of intestinal parasites was 50.4%. Intestinal parasites were significantly (p < 0.0001) more common in cat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
0
10
0
1
Order By: Relevance
“…This result highlights the importance of environmental contamination (Afonso et al, 2013;Pezeshki et al, 2017). Increased prevalence of T. cati infection in outdoor cats was also demonstrated in a large-scale European study (Beugnet et al, 2014) and another recent study (Ursache et al, 2021). One possible explanation would be that owners underestimate the impact of unsupervised outdoor time, and some cats may have been falsely reported as being strictly indoor when they had access to an enclosed garden or a balcony.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…This result highlights the importance of environmental contamination (Afonso et al, 2013;Pezeshki et al, 2017). Increased prevalence of T. cati infection in outdoor cats was also demonstrated in a large-scale European study (Beugnet et al, 2014) and another recent study (Ursache et al, 2021). One possible explanation would be that owners underestimate the impact of unsupervised outdoor time, and some cats may have been falsely reported as being strictly indoor when they had access to an enclosed garden or a balcony.…”
Section: Discussionmentioning
confidence: 65%
“…Toxocara cati was the most frequently encountered parasite in this study with a prevalence of 9 %, but also throughout Europe ( Beugnet et al, 2014 ; Gianelli et al, 2017; Overgaauw and Nijsse, 2020). Reported infection rates by T. cati in domestic cats are highly variable, ranging from 3.9 % in Germany ( Raue et al, 2017 ) to 40 % in Romania ( Ursache et al, 2021 ) but remain largely inferior to those reported in stray cats, that are regularly above 45 % ( Knaus et al, 2014 ; Takeuchi-Storm et al, 2015 ; Zottler et al, 2019 ). Nevertheless, this result is similar to the one obtained in 2006 in the same area (overall prevalence 9 %) ( Gibier 2007 , unpublished results).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In felids, most T. cati infections are subclinical. In domestic cats, heavy T. cati infection can cause clinical signs including pot-bellied appearance, diarrhea, vomiting and inappetence ( ESCCAP, 2021 ; Ursache et al, 2021 ). Toxocara spp.…”
Section: Discussionmentioning
confidence: 99%
“…The zoonotic gastrointestinal nematode Toxocara cati is a common parasite infecting domestic cats as well as wild felids worldwide ( Sprent, 1956 ; Bagrade et al, 2003 ; Valdmann et al, 2004 ; Sommerfelt et al, 2006 ; Zibaei et al, 2007 ; Okulewicz et al, 2012 ; Gallas and Silveira, 2013 ; Otranto and Deplazes, 2019 ; Hou et al, 2020 ; Figueiredo et al, 2021 ; Ursache et al, 2021 ). In Finland, the prevalence of T. cati in domestic cats was estimated to be 5.4%, based on detection of eggs of the parasite in feces ( Näreaho et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%